Cardiac MRI biomarkers for Duchenne muscular dystrophy. (30th November 2018) - Magrath, Patrick; Maforo, Nyasha; Renella, Pierangelo; Nelson, Stanley F; Halnon, Nancy; Ennis, Daniel B
Duchenne muscular dystrophy (DMD) is a fatal inherited genetic disorder that results in progressive muscle weakness and ultimately loss of ambulation, respiratory failure and heart failure. Cardiac MRI (MRI) plays an increasingly important role in the diagnosis and clinical care of boys with DMD and associated cardiomyopathies. Conventional cardiac MRI biomarkers permit measurements of global cardiac function and presence of fibrosis, but changes in these measures are late manifestations. Emerging MRI biomarkers of myocardial function and structure include the estimation of rotational mechanics and regional strain using MRI tagging; T1-mapping; and T2-mapping, a marker of inflammation, edema and fat. These emerging biomarkers provide earlier insights into cardiac involvement in DMD, improving patient care and aiding the evaluation of emerging therapies.